Intellectual stimulation in transformational school leadership and teachers' self-efficacy - Fitri Yanti; Doni Subrata; Aubray Mariel Ariestho; Desi Surlitasari Dewi (Indonesian Journal of Educational Development (IJED), 2026)
This study examines intellectual stimulation in transformational school leadership and its relationship with teachers' self-efficacy. Although transformational leadership has been widely studied, limited research has examined intellectual stimulation as a distinct dimension and its contribution to teachers' self-efficacy, particularly in Indonesian public secondary schools. Grounded in transformational leadership theory and Bandura's self-efficacy framework, this study aimed to investigate that relationship and explain how such leadership is enacted in school practice. Employing a mixed-methods explanatory sequential design, quantitative data were collected from all 52 teachers through structured questionnaires that measured principals' intellectual stimulation and teachers' self-efficacy, using total sampling, and were analyzed using descriptive statistics and linear regression. Qualitative data were obtained through semi-structured interviews with 10 voluntarily selected teachers and were analyzed thematically. The quantitative findings indicate a significant positive relationship between principals' intellectual stimulation and teachers' self-efficacy. Qualitative results reveal that intellectual stimulation is manifested through encouragement to try new teaching methods, support during experimentation and failure, opportunities for professional dialogue, freedom to express alternative ideas, and the creation of psychological safety. The study concludes that intellectually stimulating leadership strengthens teachers' confidence, professional agency, and instructional improvement. These findings recommend that school principals foster psychologically safe and intellectually supportive environments to enhance teacher self-efficacy and sustainable school development.